Daya Terima dan Kandungan Gizi Cookies Sorgum (Sorghum Bicolor, L) dengan Penambahan Bayam (Amaranthus Sp.) sebagai Makanan Selingan bagi Wanita Usia Subur (WUS) - Kholida Istiqomah; Eko Farida (Universitas Airlangga, 2024)
Background: Women of reproduvtive age are an age group that is prone to experiencing nutritional problems, such as anemia. Food-based interventions utilize sufficient amounts of iron in foodstuffs, becoming one of the efforts to prevent and control iron deficiency anemia. Intervention can be done by making products as snacks in the form of cookies, which are modified by adding foods high in iron, such as sorghum (Sorghum bicolor, L), which is a type of legume with no less nutritional content than other types of legumes. such as rice, corn and wheat. Apart from that, a type of vegetable that has many benefits due to its high iron content is found in green spinach (Amaranthus sp.). Objective: This research aims to produce the best formula by making cookies made from sorghum flour with the addition of green spinach powder, which is expected to increase the nutritional and iron content as a snack for women of reproduvtive age. Methods: This research used an experimental type of research, with a Completely Randomized Design (CRD), resulting in 2 repetitions. This research was carried out in making cookies with the formulation of adding 5%, 10%, 15% and 20% spinach powder. Acceptance testing assesses the characteristics of cookies consisting of color, taste, texture and aroma using untrained panelists with the criteria of 30 women of reproduvtive age, aged 15-49 years. Testing for nutritional content includes protein (%), fat (%), carbohydrate (%) and iron (mg). Results: The cookie formula that has the best acceptability based on the characteristics of color, taste, texture and aroma, is found in F2 with the addition of 10% spinach powder. The results of the nutritional content test in 100 grams of F2 cookies are 553.86 kcal energy, 8.29% protein, 7.77% fat, 78.18% carbohydrates and 13.57 mg iron. Conclusion: Based on iron adequacy in women of reproduvtive age aged 15-49, cookies can contribute to additional iron of 3.39 mg a day, with a serving size of 25 grams of cookies. The iron content in cookies is a type of non-heme iron which has low bioavailability, so it requires enhancers and inhibitors in food, such as vitamin C and animal source foods.